2020
DOI: 10.3389/fpsyg.2020.00787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psychotherapy on Reduction of Fear of Childbirth and Pregnancy Stress: A Randomized Controlled Trial

Abstract: Introduction: The fear of childbirth (FOC) has an adverse effect on the physical and mental health of pregnant women and increases adverse maternal and fetal outcomes. Previous research reported the effect of psychological interventions such as cognitive behavioral therapy, relaxation therapies, and short-term psycho-educational intervention on FOC. We examined whether adding motivational interviewing (MI) psychotherapy to prenatal usual care (PUC) is superior to PUC alone to reduce the scores of FOC, pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 60 publications
(67 reference statements)
2
33
0
Order By: Relevance
“…In order to prevent and treat tokophobia, cognitive therapy and psycho-education with relaxation have been found to be useful [22,23]. Not only women with a high Fear of Childbirth Questionnaire score, but every pregnant woman should have access and the opportunity to have psychological consultation, followed by extensive information on pregnancy and childbirth [24].…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent and treat tokophobia, cognitive therapy and psycho-education with relaxation have been found to be useful [22,23]. Not only women with a high Fear of Childbirth Questionnaire score, but every pregnant woman should have access and the opportunity to have psychological consultation, followed by extensive information on pregnancy and childbirth [24].…”
Section: Discussionmentioning
confidence: 99%
“…Also calming virtual reality environments seem to be effective on reducing anxiety during pregnancy, but this effect was mainly seen by qualitative data of the study (Sridhar et al, 2020). A motivational interviewing (MI) psychotherapy intervention showed a large and significant effect on the reduction of fear of childbirth (Abdollahi et al, 2020 Akbarian (2018) showed that after the intervention, the mean anxiety score of the pregnant women group was significantly lower than that of the control group and this score was significantly lower in the couples group than that in the pregnant women group. This result has to be interpreted carefully, due to a weak rating.…”
Section: Categories Of Interventionsmentioning
confidence: 94%
“…There is no clearly delimitable and common definition of fear of childbirth (FOC) in the literature. It is also difficult to draw a line between subclinical, phobic and pathological levels of FOC (Abdollahi et al 2020). To give an overview over existing terms in the literature, this paper makes an attempt to define different phrases related to the term FOC.…”
Section: Definitionsmentioning
confidence: 99%
See 2 more Smart Citations